Spatial and temporal effects on the value of ecosystem services in arid and semi-arid mountain areas—A case study from Helan Mountain in Ningxia, China - Ren, Yue; Chen, Yu; Chen, Dongmei; Zhang, Hang (Frontiers in Ecology and Evolution, 2023)
In the context of global warming and the continued increase in greenhouse gas emissions, the expansion of the global arid and semi-arid zones will accelerate, and there will be a risk of further land degradation. Changes of land use are one of the human activities that cause the increase of CO2 concentration of the global atmosphere. This article takes Helan Mountain as the research object which is located in the arid and semi-arid region. It analyzes the spatial and temporal effects of land use changes, ecosystem service value and ecological risk of land use in Helan Mountain by using GIS technology and five periods of land use data in 2000, 2005, 2010, 2015 and 2020.The study results show that: First,due to land use changes in the arid and semi-arid zones, grasslands lost the largest area (in total 50,407.11 ha) during the study period. And construction land is the the highest dynamic land type that increased 22,364.73 ha. Land use generally shows a trend of increasing before decreasing, with an inevitable increase in the degree of utilization. Secondly, the total ecosystem service value decreased 0.1148 million yuan that from 5674.5490 to 5674.6638 million yuan, which shows a slight change in the overall ecosystem service value. Thirdly, the ecological risk of land use could be divided into five classes, with a transformation characteristic from high and low ecological risk to comparatively high, medium, and comparatively low ecological risk. Fourth, the western side of Helan Mountain is the principal supply area for ecosystem services in the entire study area,where is an area with high-grade ecological risk at the same time. The vulnerability and importance of this area need to be given high priority. This study will provide spatial guidelines for the protection and restoration of ecological security issues such as environmental damage and land degradation in the arid and semi-arid regions of the mountains.